N-retinylidene-N-retinylethanolamine adduct induces expression of chronic inflammation cytokines in retinal pigment epithelium cells. (August 2021) - Scimone, Concetta; Donato, Luigi; Alibrandi, Simona; Vadalà, Maria; Giglia, Giuseppe; Sidoti, Antonina; D'Angelo, Rosalia
Abstract: Blindness due to photoreceptor degeneration is observed in both genetic and acquired eye disorders. Long blue light exposure can contribute to increase levels of oxidative compounds within the retinal pigment epithelium (RPE), enhancing risk of retinal damage. In retina, reactive oxygen species contribute to the activation of inflammatory cascade. If chronic, this inflammatory response can result in photoreceptor death. Therefore, we investigated the effects of the endogenous adduct N -retinylidene- N -retinylethanolamine (A2E) on RPE cells, in order to identify the most dysregulated cytokines and their related inflammatory pathways. RPE cells were exposed to A2E and blue light for 3h and 6h. By transcriptome analysis, we identified differentially expressed genes in A2E-treated cells, when compared to untreated ones. Expression values were quantified by the Limma R package. Enrichment analysis was performed according to the "Reactome" and the Gene Ontology databases. Expression of pro-inflammatory cytokines increased after 3h of A2E treatment and pathways related to IL-6 and IL-1 signaling resulted enriched. Also the up-regulation of genes having a protective role against inflammation was observed. Moreover, our results show that ferroptosis could contribute to RPE degeneration induced by A2E and blue light. Dysregulated genes related to retinal degeneration triggered by oxidative damage and inflammatory response activation identified in this study can be considered as potential biomarkers for targeted therapies. Highlights: Blue light triggers chronic inflammation in Retinal Pigment Epithelium cells. Increase of pro-inflammatory cytokine expression is not an early event. Blue light damage most likely triggers photoreceptor death by inducing ferroptosis.